2016
DOI: 10.1371/journal.pone.0161754
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and Susceptibility to Osteoarthritis of the Knee: A Case-Control Study and Meta-Analysis

Abstract: BackgroundStudies of angiotensin-converting enzyme insertion/deletion (ACE I/D) polymorphisms and the risks of knee osteoarthritis (OA) have yielded conflicting results.ObjectiveTo determine the association between ACE I/D and knee OA, we conducted a combined case-control study and meta-analysis.MethodsFor the case-control study, 447 knee OA cases and 423 healthy controls were recruited between March 2010 and July 2011. Knee OA cases were defined using the Kellgren-Lawrence grading system, and the ACE I/D geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 78 publications
(80 reference statements)
1
14
2
Order By: Relevance
“…They [8,9] both suggested that DD genotype of the ACE gene I/D polymorphism increased the risk of knee OA in Turkish populations. Due to the conflicting findings, Lin et al [10] conducted a case–control study and meta-analysis to validate the association of I/D polymorphism with OA risk. They did not find any significant association between I/D polymorphism and knee OA in the case–control study and meta-analysis [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They [8,9] both suggested that DD genotype of the ACE gene I/D polymorphism increased the risk of knee OA in Turkish populations. Due to the conflicting findings, Lin et al [10] conducted a case–control study and meta-analysis to validate the association of I/D polymorphism with OA risk. They did not find any significant association between I/D polymorphism and knee OA in the case–control study and meta-analysis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the conflicting findings, Lin et al [10] conducted a case–control study and meta-analysis to validate the association of I/D polymorphism with OA risk. They did not find any significant association between I/D polymorphism and knee OA in the case–control study and meta-analysis [10]. It was noteworthy that they regarded the Turkish populations as Arabians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Nonetheless, the association between angiotensin-converting enzyme and KOA remains controversial. 19 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, the polymorphisms of several genes, such as angiotensin-converting enzyme, have been found to be unrelated to the susceptibility to knee OA. 4 A disintegrin and metalloproteinase 12 (ADAM12), the gene of which has been identified as a candidate gene for knee OA, plays role ADAM12 Polymorphisms in Knee Osteoarthritis in proteolysis, cellular interactions, and signal transduction. 5 After Valdes et al 6 published a study on the association of ADAM12 polymorphisms with knee OA, several studies were conducted at other centers.…”
mentioning
confidence: 99%